1999
DOI: 10.1152/ajpregu.1999.277.6.r1718
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of food intake in response to intestinal lipid is mediated by cholecystokinin in humans

Abstract: Intraduodenal fat inhibits gastric emptying and exerts early satiation in animals and humans, but it is not clear whether the effects are mediated by cholecystokinin (CCK) in humans. Here, we tested whether CCK-A receptors mediate the inhibition of fat on food intake. Two sequential, double-blind, crossover studies were performed in 24 male subjects. First, subjects received either intraduodenal fat or saline together with a preload of either water or banana shake. Second, 12 subjects received either intraduod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 34 publications
4
78
0
3
Order By: Relevance
“…Conversely, loxiglumide, a specific CCK-A receptor antagonist, stimulates calorie intake and feelings of hunger, and delays fullness. [4][5][6][7] These studies therefore provide evidence for a physiological role of CCK, acting via peripheral CCK-A receptors, in mediating satiation signals that reduce meal size and energy intake.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Conversely, loxiglumide, a specific CCK-A receptor antagonist, stimulates calorie intake and feelings of hunger, and delays fullness. [4][5][6][7] These studies therefore provide evidence for a physiological role of CCK, acting via peripheral CCK-A receptors, in mediating satiation signals that reduce meal size and energy intake.…”
Section: Introductionmentioning
confidence: 72%
“…4 Conversely, loxiglumide, a specific CCK-A receptor antagonist, stimulates calorie intake and feelings of hunger, and delays fullness. [4][5][6][7] However, as already discussed, hydrolysis of dietary triglycerides by pancreatic lipase is necessary for the release and, presumably, the function of endogenous CCK. Indeed, Matzinger et al 7 demonstrated that intraduodenal administration of fat reduced the amount of food eaten at a subsequent meal (60 min after starting the perfusion) by 20%, corresponding to a 23% reduction in calorie intake.…”
Section: Discussionmentioning
confidence: 91%
“…Dietary protein is the most satiating macronutrient in experimental meal settings (Poppitt et al, 1998), with high-protein meals increasing blood concentrations of CCK (Blom et al, 2006;Bowen et al, 2006). Fat (Matzinger et al, 1999) and to a lesser extent carbohydrate (Holt et al, 1992;Parker et al, 2005) also stimulate CCK production from I cells in the duodenum and jejunum (Buffa et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated a role for CCK and other gut peptides in the reduction of food intake and the activation of satiety mechanisms following intraintetsinal infusions of fatty acids. These robust effects have been ameliorated by both vagotomy and CCK-A receptor antagonism (7,8,15,32). Taken together, these novel findings both demonstrate the potential clinical relevance of gut-initiated satiety mechanisms in the treatment of obesity, and suggest important information on the means to best initiate them.…”
Section: Discussionmentioning
confidence: 73%
“…Numerous studies have described a reduction in food intake following infusion of fatty acids directly into the small intestine: French et al demonstrated that upper intestinal infusions of 20% oil emulsions enriched with either stearic, oleic, or linoleic acid significantly reduced food intake compared controls infused with saline, and that this reduction in food intake was accompanied with increased plasma CCK concentrations (9); Meyer et al described reductions in food intake following intraintestinal infusions of either fatty or amino acids (16); Cox et al have reported that jejunal infusions of linoleic or oleic acid elicit increased satiety, decreased food intake and decreased body weight in rats (6). Matzinger et al demonstrated that this effect is mediated by cholecystokinin, abolishing the effects of intraduodenal fat infusions on food intake with a specific CCK-A receptor antagonist (15).…”
Section: Introductionmentioning
confidence: 99%